2022
DOI: 10.4490/algae.2022.37.9.12
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and anti-inflammatory activity of fucoidan isolated from <italic>Ecklonia maxima</italic> stipe

Abstract: Enzyme-assisted hydrolysis is frequently used as a cost-effective and efficient method to obtain functional ingredients from bioresources. This study involved the enzyme-assisted hydrolyzation and purification of fucoidan from Ecklonia maxima stipe and the investigation of its anti-inflammatory activity in lipopolysaccharide (LPS)-induced RAW 264.7 cells. Fucoidans of Viscozyme-assisted hydrolysate from E. maxima (EMSFs) harvested in Jeju, Korea. Structural and chemical characterizations were performed using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Increased TGF-β production is associated with poor survival in BC because it suppresses the anti-tumor immune response and promotes metastasis through increased levels of angiogenic and connective tissue growth proteins that promote epithelial-to-mesenchymal transition, particularly in BC. It also stimulates several signaling networks involved in cell growth, and differentiation (Lee et al, 2022). In our study, the modulation exerted by LtF on Dox was demonstrated by the remarkable decrease of TGF-β in the combined treatment, as Dox has been shown to stimulate TGF-β signaling and consequently increase metastasis in BC cells (Yunita et al, 2020).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Increased TGF-β production is associated with poor survival in BC because it suppresses the anti-tumor immune response and promotes metastasis through increased levels of angiogenic and connective tissue growth proteins that promote epithelial-to-mesenchymal transition, particularly in BC. It also stimulates several signaling networks involved in cell growth, and differentiation (Lee et al, 2022). In our study, the modulation exerted by LtF on Dox was demonstrated by the remarkable decrease of TGF-β in the combined treatment, as Dox has been shown to stimulate TGF-β signaling and consequently increase metastasis in BC cells (Yunita et al, 2020).…”
Section: Discussionmentioning
confidence: 52%
“…TNF-α controls immune and inflammatory responses during the early stage of tumor development (Lee et al, 2022). In the combined treatment, there was a decrease with respect to the Dox treatment, which could be related to the modulation exerted by fucoidan, since in the simple treatment the production of this cytokine is not significant, although it is four times higher than in the untreated.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…NF-κB translocation in inflammatory conditions activates the p38-MAPK pathway, leading to a prolonged inflammation where STAT-1 plays an important role in the cytokine productions (Sun et al 2017, Bagaev et al 2019. The NF-κB and MAPK pathways are common inflammatory signaling pathways whose activation causes pro-inflammatory cytokines, including IL-6, IL-8, and TNF-α (Park et al 2015, Lee et al 2022. In this study, LPS-treated RAW 264.7 cells showed an increased NO production and iNOS2 and NF-κB expression, indicating an inflammatory response.…”
Section: A C D Bmentioning
confidence: 99%